BRIEF 4 – Economic analysis of climate-smart agriculture interventions for goat farming households in Nepal and their marginal costs of abatement - Giles, James Edward; Mwema, Emmanuel; Notenbaert, An Maria Omer (2023)
This brief conducts benefit-cost analysis for key climate-smart practices to support agenda setting for the attainment of National mitigation targets under Nepal’s updated NDC and Net-Zero strategy.